Infrared photometry and polarimetry of blazars - Holmes, Paul Anthony (The University of Edinburgh, 1985)
A sample of blazars has been studied with infrared photometry and polarimetry in the J,H & K wavebands, using the U.K.I.R.T. in Hawaii. The objects observed for this thesis are part of an ongoing monitoring programme, for which a total of 35 objects have now been studied, many for the first time with infrared polarimetry. These results have been analysed statistically and several important correlations have emerged.

Wavelength- dependent polarization has been observed in some objects, and our observations show, for the first time at infrared wavelengths, a correlation between the strength of wavelength- dependence and the polarization degree. This result, together with an analysis of night to night variations in total and polarized flux, allow us to formulate a phenomenological model for these objects. Luminosity calculations suggest that relativistic beaming is important in the most luminous objects. The exotic polarization behaviour of OJ 287, which was observed in January 1983, is explained in terms of a relatively simple two-component model.

The properties of blazars as a class are reviewed and brief histories of the individual objects are given. The results of our observations are described in detail in chapters 4 & 5. Computer simulations were performed to determine the polarization properties of various distributions of magnetic field and electron energies, and the results tabulated. Current models for the spectral and polarization properties of blazars are described in some detail. The implications of the results presented in this thesis upon these models are also discussed.